Pengembangan Storynomic Tourism dalam Upaya Meningkatkan Kualitas Pengalaman Wisatawan di Desa Wisata Ciburial - Edison, Emron; Kartika, Titing (Pusat Penelitian dan Pengabdian Kepada Masyarakat, Institut Pariwisata Trisakti, 2024)
Tourism village has a great potency to encourage the local economic growth which will provide tourist experiences. This research aims to explore the development of Storynomic Tourism as a strategy to improve the quality of tourist experiences in the Ciburial Tourism Village. The research method used is a qualitative approach. Data collection was carried out through participant observation, interviews with relevant stakeholders. The research results show that Ciburial Tourism Village has the potential for unique stories related to its history, culture and nature. By applying the Storynomics Tourism approach, this tourist destination can create a deeper tourist experience through narratives that connect interesting places. The development of Storynomics Tourism in Ciburial Tourism Village is expected to improve the quality of tourist experiences, stimulate tourist interest in visiting, and indirectly increase local economic income. This research makes a significant contribution in developing innovative and sustainable tourism development strategies at the village level. The implication of this research is providing the practical guidance for stakeholders in designing interesting and meaningful story-based tourism experiences in the Ciburial Tourism Village, and can be a reference for developing Storynomics Tourism in other tourist destinations. Keywords: tourism village, storynomics tourism, quality of tourism experience